Arab American Femininities: Beyond Arab Virgin/ American(ized) Whore - Naber, Nadine (Feminist Studies, 2006)
Keywords: 1900-1999; 1990-1999; 2000 à aujourd'hui; 2000-2009; amériques; anthropologie; anthropologie culturelle; approches et analyses; arabes-américaines; cours; discipline; discours dominant; femmes* arabes; féminisme islamique; histoire et politique; identités culturelles; intersectionnalité; premier cycle; périodes historiques; rapports sociaux de sexe; ressource en ligne; régions géographiques; sciences humaines; sex2283; système colonial; systèmes d'oppressions; thématiques; états-unis

Make Room for Daddy: Anxious Masculinity and Emergent Homophobias in Neopatriarchal Politics - Stein, Arlene (Gender and Society, 2005)
What are the sources of continuing antipathy toward homosexuality, and what might they tell us about changing forms of American masculinity? This article documents some emergent homophobias circulating among conservative activists in relation to campaigns against gay rights in the early 1990s and against gay marriage in 2004. As feminist critiques of traditional masculinity make their way into conservative rhetoric and as men struggle to define a role that maintains male authority without sounding overly authoritarian, new forms of homophobia have emerged that are compatible with conservatives' quest to be seen as compassionate protectors of the family.
Keywords: 1900-1999; 1990-1999; 2000 à aujourd'hui; 2000-2009; LGBTQIA2+; amériques; anthropologie; approches et analyses; cours; discipline; homophobie; hétérosexisme; masculinité; militance; patriarcat; premier cycle; périodes; périodes historiques; régions géographiques; sciences humaines; soc2014; systèmes d'oppressions; thématiques; violences; états-unis